2016
DOI: 10.1111/bjd.14930
|View full text |Cite
|
Sign up to set email alerts
|

Rosacea and gastrointestinal disorders: a population‐based cohort study

Abstract: Rosacea is associated with certain gastrointestinal diseases, but the possible pathogenic link is unknown. Gastrointestinal complaints in patients with rosacea should warrant clinical suspicion of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
104
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 35 publications
2
104
0
3
Order By: Relevance
“…Recent studies suggest that systemic comorbidities including coronary artery disease, hypertension, dyslipidaemia, gastrointestinal diseases, type 1 diabetes, multiple sclerosis and rheumatologic arthritis are significantly associated with rosacea . Regarding cancer risk in rosacea patients, little reliable data are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that systemic comorbidities including coronary artery disease, hypertension, dyslipidaemia, gastrointestinal diseases, type 1 diabetes, multiple sclerosis and rheumatologic arthritis are significantly associated with rosacea . Regarding cancer risk in rosacea patients, little reliable data are available.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillales can contribute to improved enteral conditions by regulating anti‐inflammatory responses, recovering gut integrity and decreasing gut permeability, and its abundance is increased in the faeces of patients with IBD compared to healthy individuals . Given that rosacea is associated with IBD, it is plausible that two diseases have an overlapping pathogenesis with regard to the aetiological implications of Lactobacillales. Previous studies have reported increased levels of Citrobacter in Crohn's disease (CD) and Desulfovibrio in ulcerative colitis (UC) .…”
Section: Discussionmentioning
confidence: 99%
“…Egeberg et al . confirm common rosacea and gastrointestinal disorder coexistence, also regarding Helicobacter pylori infection and SIBO.…”
Section: Methodsmentioning
confidence: 99%
“…However, given that Fusobacterium varium , which inhabits the enteral mucosa, was highly detected in colon tissue samples from patients with active ulcerative colitis (UC), along with increasing serum antibody levels of F. varium , a link between UC and Fusobacterium remains plausible [23]. The association between rosacea and UC has been well established by previous studies, based on the increased prevalence of UC in rosacea patients and the shared genetic background between rosacea and inflammatory bowel disease [10, 24]. In this regard, Fusobacterium may account for blood dysbiosis as well as enteral inflammation accompanied with rosacea, and thus may be a link between rosacea and UC.…”
mentioning
confidence: 99%